Thermal behavior of alternative materials used as roof and efficiency of the reflective painting on the external face - Almeida, Eduardo Alves de [UNESP]; Passini, Roberta (Imprenta Univ Antioquia, 2017)
This study was developed in order to compare the thermal behavior of different types of roofs by measuring the External Surface Temperature (EST) and the Internal Surface Temperature (IST) over the days. The experimental design was completely randomized, with five treatments: AC - Asbestos cement tiles, BA - Bamboo tiles, BAP - Bamboo tiles painted in white, FB - Vegetable fiber tiles and bitumen, FBP - Vegetable fiber tiles and bitumen painted in white, with 15 repetitions, being adopted as repetitions the days of measurement. The temperature of the internal and external roofing surfaces was collected at 8:00 am, 10:00 am, 12:00 pm, 2:00 pm, 4:00 pm and 6:00 pm. Data were analyzed by SISVAR 5.1 (R) program through the analysis of variance and Skott Knott test for comparison of means, significance level at 1%. The FB coverage showed the worst thermal performance compared to other types of coverage, with the best results observed in BAP coverage.
Keywords: Thermal efficiency; sustainability; bio-construction